KONTEN TULISAN PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI BERBASIS MASALAH - Hilda Rahmawati; Sri Widoretno; Dewi Puspita Sari (Universitas Sebelas Maret, 2016)
The research aims to improve the quality of student’s content writing in biology through implementation of Problem Based Learning (PBL) model. The research is a Classroom Action Researc carried out for 3 cycles. Subjects of this research were students of class XI MIPA 4 SMA N 7 Surakarta with the number of 31 learners. The research data was collected through writing documentation, observation and interviews. The validity of the data is performed using the technique of triangulation method. The research using qualitative descriptive analysis techniques. The results of the analysis of quality students content writing in the pre-cycle is 0; cycle 1 identified a score of 2, 3 and 4; 2 cycles identified a score of 2, 3, 4 and 5; score 3 identified a score of 1, 2, 3, 4 and 5. All quality content writing cycle 1 to cycle 3 are at level 1 in the category of writing skills. Keywords: PBL, quality of content writing, level writing skills, content writing score